Regiones imaginarias : hacia una reinterpretación de la espiritualidad (2017)
"This project was born as a personal reflection on the role played by the imagination in a spiritual relationship with God. Starting from the base of a Catholic-Christian context, an investigation was carried out that compiled subjects like psychology, art, religion, spirituality, philosophy, among others. In this way, through research (bibliographical and from the audience), was created a project that seeks to generate a reflection in front of what is the imagination and its different interpretations within the realm of the spiritual." -- Tomado del Formato de Documento de Grado.